Home-Based Transcranial Direct Current Stimulation for the Treatment of Symptoms of Depression and Anxiety in Temporal Lobe Epilepsy: A Randomized, Double-Blind, Sham-Controlled Clinical Trial - Mota, Suelen Mandelli; Amaral de Castro, Luiza; Riedel, Patrícia Gabriela; Torres, Carolina Machado; Bragatti, José Augusto; Brondani, Rosane; Secchi, Thais Leite; Sanches, Paulo Roberto Stefani; Caumo, Wolnei; Bianchin, Marino Muxfeldt (Frontiers in Integrative Neuroscience, 2021)
We conducted a double-blind randomized clinical trial in order to examine the effects and the safety of home-based transcranial direct current stimulation (tDCS) on depressive and anxious symptoms of patients with temporal lobe epilepsy (TLE). We evaluated 26 adults with TLE and depressive symptoms randomized into two different groups: active tDCS (tDCSa) and Sham (tDCSs). The patients were first submitted to 20 sessions of tDCS for 20 min daily, 5 days a week for 4 weeks and then received a maintenance tDCS application in the research laboratory once a week for 3 weeks. The intensity of the current was 2 mA, applied bilaterally over the dorsolateral prefrontal cortex, with the anode positioned on the left side and the cathode on the right side. Participants were evaluated on days 1, 15, 30, and 60 of the study using the Beck Depression Inventory II (BDI). A follow-up evaluation was performed 1 year after the end of treatment. They were also evaluated for quality of life and for anxious symptoms as secondary outcomes. The groups did not differ in clinical, socioeconomic or psychometric characteristics at the initial assessment. There was no statistically significant difference between groups regarding reported adverse effects, seizure frequency or dropouts. On average, between the 1st and 60th day, the BDI score decreased by 43.93% in the active group and by 44.67% in the Sham group (ΔBDIfinal – initial = −12.54 vs. −12.20, p = 0.68). The similar improvement in depressive symptoms observed in both groups was attributed to placebo effect and interaction between participants and research group and not to tDCS intervention per se. In our study, tDCS was safe and well tolerated, but it was not effective in reducing depressive or anxiety symptoms in patients with temporal lobe epilepsy. Clinical Trial Registration: [ClinicalTrials.gov], identifier [NCT03871842].